2018
DOI: 10.1186/s12933-018-0771-3
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 polymorphisms associated with cardiovascular risk in Uygurs with type 2 diabetes mellitus

Abstract: BackgroundType 2 diabetes mellitus (T2D), rapidly increasing to epidemic proportions, globally escalates cardiovascular disease risk. Although intensive interventions and comprehensive management of environmental risks factors for T2D are associated with reduced cardiovascular disease, such approaches are limited for individuals with high genetic T2D risk. In this study we investigated possible associations of ACE2 polymorphisms and cardiovascular risks in Uygur patients with T2D.Methods275 Uygur T2D patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
83
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(92 citation statements)
references
References 55 publications
4
83
0
5
Order By: Relevance
“…Angiotensin-converting enzyme-2 variants are associated with a wide variety of traits. It was shown that some variants in ACE2 in Uygyrs with type 2 diabetes mellitus are associated with cardiovascular risk ( Liu et al, 2018 ). These variants, such as rs1978124, rs2048683, rs233575, rs4240157, rs4646156, and rs879922, are significant cis- eQTLs for ACE2 ( Supplementary Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin-converting enzyme-2 variants are associated with a wide variety of traits. It was shown that some variants in ACE2 in Uygyrs with type 2 diabetes mellitus are associated with cardiovascular risk ( Liu et al, 2018 ). These variants, such as rs1978124, rs2048683, rs233575, rs4240157, rs4646156, and rs879922, are significant cis- eQTLs for ACE2 ( Supplementary Table S3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on 503 Caucasian diabetic subjects, rs464188 and rs4240157 SNPs were found to be associated with hypertension in both men and women cohort [41]. In another study in Uyghur population, 8 SNPs (rs1978124, rs2048683, rs2074192, rs233575, rs4240157, rs4646156, rs4646188 and rs879922) were found to be associated with T2D with SNP rs879922 as a possible common genetic loci for T2D and T2D related cardiovascular risks [42]. Genetic variant studies conducted within Chinese ethnicity found comorbidity associated several ACE2 polymorphisms (rs2285666, rs4646188, rs2074192, rs4240157, rs4830542, rs879922) [43][44][45].…”
Section: Ace2 Polymorphism and Relation To Covid-19mentioning
confidence: 99%
“…Some of the studies focused on assessing the association of the ACE2 polymorphism and cardiovascular disorders in patients with Type 2 diabetes. Studies showed evidence that type 2 diabetes with certain ACE2 variations had a higher risk of cardiovascular complications such as coronary artery disease [42], hypertension, reduced systolic function, increased left ventricular mass [43,44], dyslipidemia, carotid atherosclerosis stenosis, retinopathy [45].…”
Section: -Sars-cov-2 Ace2 and Diabetesmentioning
confidence: 99%